1999
DOI: 10.1046/j.1365-2168.1999.01034.x
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing recurrence after sigmoid volvulus

Abstract: Subtotal colectomy, carried out as the primary procedure if there is concomitant megacolon or megarectum, might reduce the risk of recurrent sigmoid volvulus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
64
1
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 16 publications
0
64
1
4
Order By: Relevance
“…Colonic resection for non-gangrenous sigmoid volvulus has an acceptably low rate of complications, particularly when it is done as a semi-elective procedure, i.e., subsequent to endoscopic detorsion and deflation [20] . Finally, recurrent volvulus after resection has been reported at an incidence rate ranging from 24% to 33% of cases [5,18] . In conclusion, even though sigmoid volvulus causing intestinal obstr uction is frequently encountered in endoscopic decompression, this condition should be definitely treated by surgery; and only occasionally in patients with advanced age, lack of bowel symptoms, having multiple co-morbidities might surgical repair not be considered.…”
Section: S I G M O I D Vo L V U L U S I S T H E M O S T C O M M O N Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Colonic resection for non-gangrenous sigmoid volvulus has an acceptably low rate of complications, particularly when it is done as a semi-elective procedure, i.e., subsequent to endoscopic detorsion and deflation [20] . Finally, recurrent volvulus after resection has been reported at an incidence rate ranging from 24% to 33% of cases [5,18] . In conclusion, even though sigmoid volvulus causing intestinal obstr uction is frequently encountered in endoscopic decompression, this condition should be definitely treated by surgery; and only occasionally in patients with advanced age, lack of bowel symptoms, having multiple co-morbidities might surgical repair not be considered.…”
Section: S I G M O I D Vo L V U L U S I S T H E M O S T C O M M O N Cmentioning
confidence: 99%
“…Furthermore, various procedures have been adopted for sigmoid volvulus in adult patients, such as mesosigmoidoplasty, sigmoidopexy, tube sigmoid colostomy or mesocoloplasty. In patients with sigmoid resection a recurrence is possible in approximately 25% to 35% cases [5,13,18] . The mortality rate ranges from 1% to 9% for viable colon [15,19] , and 25% for gangrenous volvulus [15] .…”
Section: S I G M O I D Vo L V U L U S I S T H E M O S T C O M M O N Cmentioning
confidence: 99%
“…Harbrecht and Fry (17) showed similar results related to the recurrence of SV in a 3-patient group. According to the reports of Morrissey and Deitch (18), Chung et al (20), and Strom et al (21), the explanation for the high recurrence rate is that these patients generally have abnormal colonic motility or atony, in addition to a residual dilated colon section proximal to the site of the sigmoid resection; thus, limiting the resection appears to represent a partial solution. Therefore, a subtotal (18,21) or total (16) colectomy is advocated as the primary choice in the treatment of SV patients with megacolon.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these diseases are known causes of the recurrence of SV, particularly in patients in whom nonoperative detorsion or limited bowel resection is performed (16)(17)(18)(20)(21)(22)(23). In a 6-patient series, Ryan (16) reported that the history was longer, the episodes were more severe, the nonoperative treatment was less effective, and recurrence was more frequent in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Therefore, nonoperative treatment should be used primarily to move patients from emergency surgery status to semielective surgery status. 8 Because SV is most common among elderly and frail patients, less invasive surgery is desirable after the urgent situation is addressed with conservative treatment.…”
mentioning
confidence: 99%